1,25-Dihydroxyvitamin D3-Conditioned CD11c+ Dendritic Cells are Effective Initiators of CNS Autoimmune Disease - Besusso, Dario; Saul, Louise; Leech, Melanie D.; O’Connor, Richard A.; MacDonald, Andrew S.; Anderton, Stephen M.; Mellanby, Richard J. (Frontiers in Immunology, 2015)
Dendritic cells (DC) play a crucial role in regulating T cell activation. Due to their capacity to shape the immune response, tolerogenic DC have been used to treat autoimmune diseases. In this study we examined whether 1,25 dihydroxyvitamin D3 conditioned bone marrow derived DC (VitD-BMDC) were able to limit the development of autoimmune pathology in experimental autoimmune encephalomyelitis (EAE). We found that VitD-BMDC had lower expression of MHC class II and co-stimulatory molecules and were less effective at priming autoreactive T cells in-vitro. Using our recently described BMDC driven model of EAE, we demonstrated that VitD-BMDC had a significantly reduced ability to initiate EAE. We found that the impaired ability of VitD-BMDC to initiate EAE was not due to T cell tolerisation. Instead, we discovered that the addition of 1,25(OH)2D3 to BMDC cultures resulted in a significant reduction in the proportion of CD11c+ cells. Purified CD11c+VitD-BMDC were significantly less effective at priming T cells in-vitro yet were similarly capable of initiating EAE as vehicle treated CD11c+BMDC. This study demonstrates that in-vitro assays of DC function can be a poor predictor of in-vivo behaviour and that CD11c+VitD-BMDC are highly effective initiators of an autopathogenic T cell response.